Respuesta :

I'm going to solve this step by step:

Given: w=x(v_2 - v_1)

          w/x=v_2-v_1

          v_2=w/x+v_1

Given :

  • [tex] \tt w = x(v_2 - v_1) [/tex]

To Find :

  • [tex] \tt v_2 = ?[/tex]

Solution :

[tex] \tt \dashrightarrow w = x(v_2 - v_1) [/tex]

[tex] \tt \dashrightarrow \dfrac{w}{x} = v_2 - v_1[/tex]

[tex] \tt \dashrightarrow \dfrac{w}{x} + v_1= v_2[/tex]

[tex] \tt \dashrightarrow v_2 = \dfrac{w}{x} + v_1[/tex]

[tex] \large \underline{\boxed{\bf{v_2 = \dfrac{w}{x} + v_1}}}[/tex]

Hence, value of [tex] \tt v_2 = \dfrac{w}{x} + v_1[/tex]